Unmet Occupational Health Needs of Malawian Ex-Miners from the South African Gold Mines - Rinila Haridas; Rodney Ehrlich; Yotam Moyo; Annalee Yassi; Jerry Spiegel; Khumbo Kalua (Annals of Global Health, 2025)
Background: From early in its history, gold mining in South Africa involved recruiting hundreds of thousands of workers from Malawi and other neighbouring countries to work in an environment conducive to high rates of tuberculosis and silicosis. Official recruitment from Malawi ended in the 1990s, depriving large numbers of these migrant miners of their livelihood, with limited or no access to employment-linked social benefits and services. Objectives: To describe barriers faced by Malawian migrant ex-gold miners in accessing social benefits related to occupational lung disease and related health services and medical examinations, and to identify needed actions. Methods: This study, conducted in the Blantyre region of Malawi, draws from field observations and interviews with 14 ex-gold miners who had worked on South African gold mines, supplemented by five key informant interviews. Data were analysed using a phenomenological and thematic analysis approach. Findings: Ex-migrant miners described precarious livelihoods and difficulty accessing employment-linked benefit examinations and health services. They are largely uncertain about their entitlements related to their past work in South Africa and the means for pursuing such rights. The division of responsibility within South Africa and between the governments of South Africa and Malawi has resulted in confusion and misinformation. Within Malawi, scarcity of funding, administrative hurdles and limited occupational lung disease expertise are barriers to expanding current services for ex-migrant miners as well as ex-miners from Malawian mines. Conclusions: A number of actions are needed: coordination between the Malawian government and South African agencies; integration of occupational health services, including for migrant ex-gold miners, into Malawi’s public health system; education of ex-gold miners and their dependents about their rights and related processes and the provision of relief aid through local and external support. Financial involvement of the South African mining industry that profited from the services of migrant miners is required to alleviate the burden on publicly funded health systems.